2021
DOI: 10.1101/2021.11.28.470293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protective immunity of the primary SARS-CoV-2 infection reduces disease severity post re-infection with Delta variants in Syrian hamsters

Abstract: Delta variant has evolved to become dominant SARS-CoV-2 lineage worldwide and there are reports of secondary infections with varying severity in vaccinated and unvaccinated naturally recovered COVID-19 patients. As the protective immunity following the infection wanes within few months, studies of re-infection after prolonged duration is needed. Hence we assessed the potential of re-infection by Delta, Delta AY.1 and B.1 in COVID-19 recovered hamsters after 3 months of infection. Re-infection with Delta and B.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…2a). These data confirm waning immunity to mRNA vaccination against SARS-CoV-2 in the golden Syrian hamster, as was shown recently after natural infection 28,29 . The similarity to which serum NAb titers were generated and then waned relative to humans provides support for the hamster as a high-fidelity model for studying booster vaccination 30,31 .…”
Section: Main Textsupporting
confidence: 90%
See 1 more Smart Citation
“…2a). These data confirm waning immunity to mRNA vaccination against SARS-CoV-2 in the golden Syrian hamster, as was shown recently after natural infection 28,29 . The similarity to which serum NAb titers were generated and then waned relative to humans provides support for the hamster as a high-fidelity model for studying booster vaccination 30,31 .…”
Section: Main Textsupporting
confidence: 90%
“…Collectively, these data show that hamsters with waning immunity to bnt162b2 are highly susceptible to URT infection by Delta VOC but clear it faster than unvaccinated animals and are modestly- to highly susceptible to infection and associated inflammation in the lung, respectively. A qualitatively similar response was recently reported in hamsters with waning immunity to natural infection 28,29 .…”
Section: Main Textsupporting
confidence: 88%
“…Mucosal COVID-19 vaccines have been experimentally shown to reduce upper respiratory shedding, but not transmission, when assessed in a single contact transmission chain setting [ 30 32 ]. In addition, hamster studies have shown that previous infection protects against disease, but not upper respiratory tract replication, after homologous and heterologous reinfection [ 27 , 34 36 ]. Similar dynamics were observed in our experimental setup.…”
Section: Discussionmentioning
confidence: 99%